Supra- and Infratentorial Extradural Hematoma: A Series of Three Cases with Literature Review - Ranjan, Nitish; Maurya, Ved Prakash; Bhaisora, Kamlesh Singh; Verma, Pawan Kumar; Kumar, Raj (Indian Journal of Neurotrauma, 2024)
The extradural hematoma (EDH) of the posterior fossa is a rare clinical condition in head injury cases. The posterior fossa extradural hematoma (PFEDH) contributes to not more than 4 to 8% of all the EDH encountered in traumatic brain injury. The limited volume of the posterior fossa leads to early clinical deterioration and, if not subjected to timely intervention, may be fatal. This rapid deterioration is because of significant compression over the brainstem and cervicomedullary junction as well as obstructive hydrocephalus. The PFEDHs are often associated with fracture of the occipital bone, which may lead to the extension of hematoma in the supratentorial and infratentorial spaces. The traumatic supra- and infratentorial EDH (TSIEDH) constitutes less than 2% of all the EDH. Limited literature is available regarding TSIEDH, and the majority are in the form of isolated case reports. We share our experience of three cases over the last 5 years from a tertiary care referral institute with a literature review of TSIEDH. Two of these cases were managed nonoperatively, and one underwent surgical evacuation of hematoma. In the present study, we share our experience regarding prompt diagnosis and management of this particular subset of traumatic brain injury patients. We also describe the surgical technique for evacuation of TSIEDH. Early diagnosis and prompt surgical intervention can be life-saving as these hematomas may have a benign clinical presentation but rapid clinical deterioration.
Keywords: extradural hematoma; supratentorial; infratentorial; evacuation; traumatic brain injury